Evolution from Bioinert to Bioresorbable: In Vivo Comparative Study of Additively Manufactured Metal Bone Scaffolds - Juncen Zhou; Elias Georgas; Yingchao Su; Jiayi Zhou; Nadja Kröger; Felix Benn; Alexander Kopp; Yi‐Xian Qin; Donghui Zhu (Advanced Science, 2023)
Abstract Additively manufactured scaffolds offer significant potential for treating bone defects, owing to their porous, customizable architecture and functionalization capabilities. Although various biomaterials have been investigated, metals – the most successful orthopedic material – have yet to yield satisfactory results. Conventional bio‐inert metals, such as titanium (Ti) and its alloys, are widely used for fixation devices and reconstructive implants, but their non‐bioresorbable nature and the mechanical property mismatch with human bones limit their application as porous scaffolds for bone regeneration. Advancements in additive manufacturing have facilitated the use of bioresorbable metals, including magnesium (Mg), zinc (Zn), and their alloys, as porous scaffolds via Laser Powder Bed Fusion (L‐PBF) technology. This in vivo study presents a comprehensive, side‐by‐side comparative analysis of the interactions between bone regeneration and additively manufactured bio‐inert/bioresorbable metal scaffolds, as well as their therapeutic outcomes. The research offers an in‐depth understanding of the metal scaffold‐assisted bone healing process, illustrating that Mg and Zn scaffolds contribute to the bone healing process in distinct ways, but ultimately deliver superior therapeutic outcomes compared to Ti scaffolds. These findings suggest that bioresorbable metal scaffolds hold considerable promise for the clinical treatment of bone defects in the near future.